Rideability analysis of mechanical elastic wheel in damaged conditions. (June 2022) - Zhang, Chenxi; Zhao, Youqun; Lin, Tao; Sun, Xinyu
Highlights: The rideability of mechanical elastic wheel is analyzed at first time. Mechanical elastic wheel can be used in damaged conditions. The rideability can be analyzed by the rigid-flexible coupling ring model with travelling mode superposition method. The axisymmetric damage of the wheel is better than neighboring chain damage. The simulation time cost of ring model is less than that of finite element model. Abstract: In this paper, it is first time to study rideability of mechanical elastic wheel (MEW) in damaged conditions and discuss whether the wheel with local damage conditions will be failure during running. This paper is first time to propose a rideability evaluation method of damaged MEW. For getting the parameters about displacement acceleration of rings and tensile force of chains required from the evaluation method, a rigid-flexible coupling model 'ring model' of running MEW was established, the solution method of the model was also given by travelling mode superposition method. The ring model was compared with the experiment and finite element method to verify its accuracy. With using the verified ring model, the rideability simulation was analyzed under eight kinds of speeds and six kinds of damaged working conditions. The results show that: MEW with one or two damaged chains still has the receptible rideability and is not failure, and it provides security for the safe driving of vehicles in emergency situations; when damaging three chains, the wheel can be used to run at low speeds, the rideability of wheel at high speeds will deteriorate and the wheel will be failure; the rideability of MEW with axisymmetric chain damage is better than that with neighboring chain damage; it also finds that the simulation calculation time of ring model is much lower than that of finite element method, the time cost will be saved.